Experimental Infection Using Mouse-Adapted Influenza B Virus in a Mouse Model - Prokopyeva, Elena (Viruses, 2020)
Every year, influenza B viruses (IBVs) contribute to annual illness, and infection can lead to serious respiratory disease among humans. More attention is needed in several areas, such as increasing virulence or pathogenicity of circulating B viruses and developing vaccines against current influenza. Since preclinical trials of anti-influenza drugs are mainly conducted in mice, we developed an appropriate infection model, using an antigenically-relevant IBV strain, for furtherance of anti-influenza drug testing and influenza vaccine protective efficacy analysis. A Victoria lineage (clade 1A) IBV was serially passaged 17 times in BALB/c mice, and adaptive amino acid substitutions were found in hemagglutinin (HA) (T214I) and neuraminidase (NA) (D432N). By electron microscopy, spherical and elliptical IBV forms were noted. Light microscopy showed that mouse-adapted IBVs caused influenza pneumonia on day 6 post inoculation. We evaluated the illness pathogenicity, viral load, and histopathological features of mouse-adapted IBVs and estimated anti-influenza drugs and vaccine efficiency in vitro and in vivo. Assessment of an investigational anti-influenza drug (oseltamivir ethoxysuccinate) and an influenza vaccine (Ultrix(®), SPBNIIVS, Saint Petersburg, Russia) showed effectiveness against the mouse-adapted influenza B virus.